Decision Support System for Community Housing Subsidy Recipients - Adhi Nugraha; Alvian Widianto; M. Irfan; M. Nasar; Merinda Lestandy (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
Human needs consist of primary, secondary, and tertiary needs. In primary needs, the house is one of the most critical primary needs in supporting one’s life. However, not all residents in Indonesia can meet these needs. Therefore, the government provides subsidized housing ownership programs for people with low income. This study aims to propose a decision support system in determining the proper housing subsidy recipients. The method used in weighting is Analytic Hierarchy Process (AHP). Previous research was still limited to the selection of subsidized housing for developers and potential buyers. This method is projected to provide results in the form of a priority sequence of alternative solutions based on test results. The results were considered capable of providing a better solution for selecting prospective recipients of the housing subsidy program.